An examination of smartphone usage and addiction among final-year medical faculty students - Aysun Aras; Nurdan Torun (Universitas Negeri Padang, 2021)
The purpose of this study was to determine levels of smartphone addiction among final-year medical faculty students. One hundred eighty students participated in this cross-sectional study. The Smartphone Addiction Scale was used to evaluate smartphone addiction levels and participants' sociodemographic characteristics. Descriptive statistics and the chi-square Kruskal-Wallis and Mann-Whitney U tests were applied. The mean addiction score was significantly higher in women than in men (p≤0.05). The students in the study mainly (71.1%) used smartphones to access the internet. Total addiction levels were significantly higher among participants who checked their phones immediately upon waking (p<0.05). Studies of smartphone addiction are insufficient, and different results may be yielded by studies on the subject from different universities.